Precise Layer Control and Electronic State Modulation of a Transition Metal Dichalcogenide via Phase‐Transition‐Induced Growth. Issue 48 (26th July 2021) - Sohn, Ahrum; Kim, Changhyun; Jung, Jae‐Hwan; Kim, Jung Hwa; Byun, Kyung‐Eun; Cho, Yeonchoo; Zhao, Pin; Kim, Sang Won; Seol, Minsu; Lee, Zonghoon; Kim, Sang‐Woo; Shin, Hyeon‐Jin
Abstract: Wafer‐scale growth of transition metal dichalcogenides with precise control over the number of layers, and hence the electronic state is an essential technology for expanding the practical application of 2D materials. Herein, a new growth method, phase‐transition‐induced growth (PTG), is proposed for the precisely controlled growth of molybdenum disulfide (MoS2 ) films consisting of one to eleven layers with spatial uniformity on a 2 in. wafer. In this method, an energetically unstable amorphous MoS x O y (a‐MoS x O y ) phase is effectively converted to a thermodynamically stable crystalline MoS2 film. The number of MoS2 layers is readily controlled layer‐by‐layer by controlling the amount of Mo atoms in a‐MoS x O y, which is also applicable for the growth of heteroatom‐inserted MoS2 . The electronic states of intrinsic and Nb‐inserted MoS2 with one and four layers grown by PTGare are analyzed based on their work functions. The work function of monolayer MoS2 effectively increases with the substitution of Nb for Mo. As the number of layers increases to four, charge screening becomes weaker, dopant ionization becomes easier, and ultimately the work function increases further. Thus, better electronic state modulation is achieved in a thicker layer, and in this respect, PTG has the advantage of enabling precise control over the film thickness. Abstract : Phase‐transition‐induced growth is effective for synthesizing layer‐controlled and electronic‐state‐modulated MoS2 films. The energetically unstable amorphous MoS x O y is efficiently converted to a thermodynamically stable crystalline MoS2 film on a wafer scale with excellent uniformity. The number of layers is precisely controlled layer‐by‐layer from one to eleven layers, which is applicable in the growth of both intrinsic and heteroatom‐inserted MoS2 .